Abundance and distribution of tiger prey base at Bardia- Katarniyaghat corridor forest, Nepal - Karki, A.; Jnawali, S. R.; Adhikari, S.; Sharma, S. K. (Banko Janakari, 2013)
Not available. DOI: http://dx.doi.org/10.3126/banko.v22i2.9199 Banko Janakari: A Journal of Forestry Information for Nepal Vol. 22, No. 2, 2012 November Page:53-56 Uploaded date: 12/1/2013